Innovative christian strategies for confronting syncretic practices in selected methodist and pentecostal churches in Abogeta division, Meru county, Kenya - Mwiti, Salome Gathoni; Nderitu, Joyce W.; Wambugu, Simon Nderitu (International Journal of Social Science and Humanities Research, 2015)
A study was carried out to establish the Christian strategies that confront syncretic practices in the church a case of selected mainline Methodist and Pentecostal churches. The objectives of the study were; to identify the forms of syncretism practices practiced by Christian churches in Kenya, to find out the reasons why Christians still practice syncretic practices in Kenya and to evaluate Christian strategies that confront syncretic practices in the churches in Kenya. The target population for this study was all the pastors and sampled members in Pentecostal and Methodist churches in Abogeta division. The study established that; the majority of the respondents was satisfied with the beliefs and practices of the church, of the respondents indicated that some of the church members did visit diviners. The study further established that some of the church members did believe in astrology and fortune-telling, some of the preachers did preach modified versions of the gospel and that some of the Church members were involved in traditional religious practices. The study established that some of the participants were not satisfied spiritually, and could have resulted to syncretic practices, for satisfaction, the preachers had disoriented the gospel to suit their needs, as was revealed by the majority of the participants, the gospel preached in the churches did not meet the spiritual needs of the church members and that the members of the church did not feel protected by their gospel. The study established that; the preachers did teach against syncretism using familiar accounts from the Bible, the church leaders did teach the supremacy of Jesus Christ, and the church leaders should teach and apply salvation by grace through faith, to confront syncretic practices. The study further concluded that spiritual dissatisfaction, preachers not meeting the spiritual needs of the members of the congregation, the Christians did not feel protected by the gospel and the insecurity that led to Christians resulting to witchdoctors. The study recommended that; the preachers should adhere to the actual content of the bible, and lead the Christians to the way of true Christianity, through spiritual nurturing and growth by the preachers
Keywords: Syncretism; contextualization; denominational challenges